Induction of Plasmodium-Specific Immune Responses Using Liposome-Based Vaccines - Ssemaganda, Aloysious; Giddam, Ashwini Kumar; Zaman, Mehfuz; Skwarczynski, Mariusz; Toth, Istvan; Stanisic, Danielle I.; Good, Michael F. (Frontiers in Immunology, 2019)
In the development of vaccines, the ability to initiate both innate and subsequent adaptive immune responses need to be considered. Live attenuated vaccines achieve this naturally, while inactivated and sub-unit vaccines generally require additional help provided through delivery systems and/or adjuvants. Liposomes present an attractive adjuvant/delivery system for antigens. Here, we review the key aspects of immunity against Plasmodium parasites, liposome design considerations and their current application in the development of a malaria vaccine.